Heterotic potential and combining ability of Coffea arabica L - Vinícius Teixeira Andrade; Francislei Vitti Raposo; Gladyston Rodrigues Carvalho; André Dominghetti Ferreira; Cleidson Alves da Silva; Jéfferson de Oliveira Costa; César Elias Botelho (Scientific Reports)
Abstract The use of hybrid vigor or heterosis in Coffea arabica L. cultivation has gradually been commercially explored worldwide since research has evolved in understanding this phenomenon and the vegetative propagation techniques or male-sterility making its use viable. Additionally, coffee producers adopting this technology have continuously increased. Therefore, we studied the existence and magnitude of heterosis and estimate the combining ability of parents in bi-parental crosses. The experiment was installed in 2019 using a randomized block design with three replications, with the experimental plot consisting of six plants. The experimental treatments consisted of 90 hybrids and 34 parental lines in which the grain yield in bags of processed coffee per hectare was evaluated according to the cumulative result of the first three harvests. Significant differences were observed between the 124 treatments, with the mean accumulated productivity values of the best hybrids surpassing those of the four most used commercial cultivars by more than 74 bags of coffee per hectare. The average yield mean heterosis was 64.2%, varying from − 26.1 to 184.4. Both the general combining ability (GCA) and the specific combining ability (SCA) were statistically significant, with the best-performing lines identified as potential parents being ‘Acauã Novo’, ‘IAC 125 RN’, ‘MGS Liberdade’, ‘Catiguá MG2’, and ‘Sarchimor MG 8840’. Promising hybrids for commercial exploitation were identified with a productive advantage of 30% relative to the best commercial standard cultivar, reinforcing the potential of this technology for C. arabica L. cultivation future.